Battery binder as well as preparation method and application thereof

By introducing sulfonate groups on SEBS, sulfonated modified battery binder is provided, which solves the problems of pollution and poor conductivity of existing lithium battery binders in high decomposition and alkaline environments, and achieves the following: Efficient electrochemical properties and environmentally friendly recycling in water-based and oil-based environments.

CN119242233APending Publication Date: 2025-01-03HUNAN HUMP NEW ENERGY CO LTD

Patent Information

Application Number
CN202411328842.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing lithium battery binders have pollution and corrosion problems in high decomposition, alkaline environment and recycling, and have poor electrical conductivity, which affects battery performance.

Method used

Sulfonated modified SEBS is used as a battery binder to provide ionic conductivity by introducing sulfonate groups, improve electrochemical performance, and is suitable for both aqueous and oily environments to reduce the risk of pollution.

Benefits of technology

Improves the electrochemical performance of lithium-ion and sodium-ion batteries, including first-time efficiency, capacity and circulation performance, reduces internal resistance, enhances heat and aging resistance, and simplifies battery production and recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242233A_ABST
    Figure CN119242233A_ABST
Patent Text Reader

Abstract

The invention discloses a battery binder as well as a preparation method and application thereof, and belongs to the technical field of new energy materials. The battery binder provided by the invention is sulfonated modified SEBS (Styrene-Ethylene-Butylene-Styrene) and comprises a main chain and a grafting group, the main chain is SEBS, and the SEBS has phenyl groups; and the grafting group is grafted on the phenyl group and comprises-SO3H and / or-SO3M. The battery binder provided by the invention can adapt to aqueous and oily slurry environments of a positive electrode and a negative electrode, and has relatively strong cohesiveness and ionic conductivity, so that the first effect, the capacity, the cycle performance and the rate capability of a secondary battery comprising the battery binder can be improved. The invention also provides a preparation method and application of the battery binder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a battery binder and a preparation method and application thereof. Background Art

[0002] Lithium battery binder is an important component in electrode production, usually one or more polymer compounds. Its main functions are to bond and maintain active materials, enhance the contact between active materials and conductive agents and between active materials and current collectors, and also stabilize the structure of the pole piece. Because the volume of the positive and negative electrodes of lithium-ion batteries will expand and shrink during the cycle, it is also hoped that the binder can play a certain buffering role in the volume change in actual production. Overall, the properties of the binder, such as adhesion, flexibility, alkali resistance, hydrophilicity, etc., directly affect the performance of lithium batteries; therefore, the industry requires that lithium battery binders have a small ohmic resistance, stable performance in the electrolyte, no expansion, no looseness, no powdering, and require the binder to have relatively excellent bonding properties; in this way, by adding the optimal amount and the best adapted type of binder, a larger capacity, a longer cycle life and a lower internal resistance can be obtained, which ultimately improves the battery's cycle performance, fast charging and discharging capabilities, and reduces the battery's internal pressure.

[0003] At present, the commonly used lithium battery binders in the commercial market are divided into two categories: oil-soluble and water-soluble. The most widely used oil-soluble binders are polyvinylidene fluoride (PVDF) homopolymers and copolymers, which use organic solvents as dispersants, while the most widely used water-soluble binders are styrene butadiene rubber (SBR) emulsion binders, which use water as dispersants.

[0004] However, the commonly used oil-soluble binders and water-soluble binders have inevitable disadvantages. Specifically, when PVDF is used as a binder, there are the following disadvantages: PVDF contains F, so an organic solvent is required, generally N-methylpyrrolidone, which is not environmentally friendly and has a high cost; at the same time, PVDF is prone to jelly under alkaline conditions, resulting in the scrapping of the slurry, and most lithium or sodium positive electrode materials are alkaline, so they need to be used stably under very strict humidity control conditions; in addition, when recycling batteries using PVDF, there are corrosion and pollution problems caused by F. When SBR is used as a binder, there are the following disadvantages: SBR contains unsaturated double bonds, which will oxidize and decompose above 4V and cannot be used for the positive electrode; at the same time, the pole piece made of SBR has a relatively large rebound, and its own ductility is poor. When used for silicon-carbon materials with large volume changes, fatigue failure is prone to occur, and the aging resistance is poor. Most importantly, whether PVDF or SBR is used as a binder, there is a disadvantage of poor conductivity, which is not conducive to the formation of a good conductive network for the pole piece.

[0005] Based on the above problems, there is an urgent need to develop an adhesive that can be used in water-based systems, does not contain F, is stable under high voltage, has good processing performance, and has good electrical properties. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a battery binder that can adapt to the aqueous and oily slurry environments of positive and negative electrodes and has strong adhesion and ion conductivity, thereby improving the first efficiency, capacity, cycle performance and rate performance of a secondary battery including the battery binder.

[0007] The invention also provides a method for preparing the battery binder.

[0008] The present invention also provides application of the battery binder.

[0009] According to an embodiment of the first aspect of the present invention, a battery binder is provided, wherein the battery binder is sulfonated modified SEBS.

[0010] The battery binder according to the embodiment of the present invention has at least the following beneficial effects:

[0011] In conventional technology, some secondary batteries directly use SEBS as a binder. However, SEBS is insulating, which will lead to high internal resistance of the secondary battery, serious polarization of the secondary battery, and poor cycle performance. In the battery binder provided by the present invention, sulfonated modified SEBS is used as the battery binder, and the sulfonate group (-SO3H) or sulfonate group (-SO3M) thereon can be ionized to provide ionic conductivity, thereby reducing the internal resistance of the secondary battery and improving its electrochemical performance.

[0012] When SEBS is directly used as a battery binder, since SEBS is only oil-soluble and not water-soluble, it can only be applied to oily systems. In the battery binder provided by the present invention, the sulfonate group (or sulfonate group) after sulfonation is hydrophilic, so the battery binder can be used in an aqueous environment, which can reduce pollution to a certain extent. At the same time, it can also form an oil-based glue, so it is still applicable to water-sensitive materials.

[0013] Compared with traditional binders such as PVDF, the battery binder provided by the present invention is stable to alkali and will not cause slurry instability due to the alkalinity of the material; when the battery is recycled, since the battery binder provided by the present invention does not contain fluorine, its pollution and corrosiveness are relatively weak and it is easier to handle.

[0014] Compared with binders such as SBR, the battery binder provided by the present invention does not contain carbon-carbon double bonds, has good stability, can be used in the positive electrode, and also has good heat resistance and aging resistance. From another perspective, the battery binder provided by the present invention has the dual advantages of SBR and CMC.

[0015] In summary, the battery binder provided by the present invention has good heat resistance, aging resistance, adhesion, and excellent electrical properties. It can use water or organic solvents as dispersants and be used to make positive and negative electrode sheets of lithium-ion batteries or sodium-ion batteries. It can optimize the electrochemical properties of secondary batteries, including initial efficiency, battery internal resistance, capacity utilization, cycle performance, etc., while reducing the production environment requirements for secondary battery sheet production.

[0016] According to some embodiments of the present invention, the battery binder comprises a main chain and a grafted group;

[0017] The main chain is SEBS, and the SEBS has a phenyl group;

[0018] The grafted group is grafted onto the phenyl group and includes -SO3H and / or -SO3M.

[0019] According to some embodiments of the present invention, in the battery binder, the grafting rate of the grafted group is 15-35%, for example, about 18%, 19%, 20%, 22%, 23%, 25%, 26%, 27%, 28%, 30%, 32% or about 33%.

[0020] According to some embodiments of the present invention, when the grafted group includes -SO3M, M includes at least one of Li, Na and K.

[0021] According to some embodiments of the present invention, when the grafted group includes -SO3M, the molar percentage (basification rate) of -SO3M in the grafted group is 0 to 100%, for example, about 30%, 40%, 50%, 60%, 70%, 80% or about 90%.

[0022] According to some embodiments of the present invention, the tensile strength at break of the battery binder is 15-25 MPa, for example, about 16 MPa, 17 MPa, 18 MPa, 19 MPa, 20 MPa, 21 MPa, 22 MPa, 23 MPa or about 24 MPa.

[0023] According to some embodiments of the present invention, the elongation at break of the battery adhesive is 410-470%, for example, about 120%, 430%, 440%, 450% or about 460%.

[0024] According to some embodiments of the present invention, the thermal deformation temperature of the battery adhesive is 115-130° C. For example, it may be about 118° C., 120° C., 122° C., 125° C. or about 128° C.

[0025] According to some embodiments of the present invention, the number average molecular weight Mn of the battery binder is 80,000 to 200,000, for example, about 85,000, 90,000, 100,000, 150,000, 160,000 or about 170,000.

[0026] According to an embodiment of the second aspect of the present invention, a method for preparing the battery binder is provided, the method comprising the following steps:

[0027] S1. reacting SEBS with a sulfonating agent to obtain sulfonated SEBS;

[0028] Or, after step S1, perform step S2:

[0029] S2. reacting the sulfonated SEBS with a base.

[0030] The typical mechanism of the preparation method is explained as follows:

[0031] The typical molecular chain structure of SEBS is as follows:

[0032]

[0033] The subscripts m, x1, x2, etc. can all be adjusted in actual production.

[0034] After sulfonation, the typical structural formula of the obtained sulfonated SEBS is as follows:

[0035]

[0036] That is, a sulfonate group is grafted at the para position of the phenyl group.

[0037] After step S2 reacts with a base, the typical structural formula of the product is as follows:

[0038]

[0039] That is, in step S2, the actual reaction is the reaction between the base and the sulfonate group.

[0040] Therefore, in actual production, the proportion of -SO3M in the grafted group can be controlled by controlling whether step S2 is performed and the proportion of the base added in step S2.

[0041] Since the preparation method adopts all the technical solutions of the battery binder of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.

[0042] According to some embodiments of the present invention, in step S1, the SEBS is a copolymer of styrene and other olefins, wherein the mass percentage of styrene is 15-55%, for example, about 20%, 30%, 40%, 45% or about 50%.

[0043] According to some embodiments of the present invention, in step S1, the reaction is carried out in an organic solvent, wherein the organic solvent comprises chloroform.

[0044] According to some embodiments of the present invention, in step S1, the mass concentration of the SEBS in the organic solvent is 8-14%, for example, about 10% or about 12%.

[0045] According to some embodiments of the present invention, in step S1, the sulfonation reagent is a combination of acetic anhydride and concentrated sulfuric acid (hereinafter referred to as sulfonation route one). In sulfonation route one,

[0046] The molar ratio of the acetic anhydride to the phenyl group in the SEBS is 75 to 200:100, for example, about 1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.8:1 or about 1.9:1.

[0047] The molar ratio of acetic anhydride to concentrated sulfuric acid is 1:0.8-1.2; for example, it can be about 1::1.

[0048] In step S1, the reaction time is 2 to 12 hours, for example, about 4 hours, 6 hours, 8 hours or about 10 hours.

[0049] In step S1, the reaction temperature is 5 to 35°C, for example, about 10°C, 15°C, 20°C, 25°C or about 30°C.

[0050] According to some embodiments of the present invention, in step S1, the sulfonation reagent includes sulfur trioxide (hereinafter referred to as sulfonation route 2). In sulfonation route 2,

[0051] The molar ratio of the sulfur trioxide to the phenyl group in the SEBS is 0.15 to 0.60:1, for example, about 0.2:1, 0.3:1, 0.4:1 or about 0.5:1.

[0052] The reaction time of step S1 is 30 to 180 minutes.

[0053] The reaction temperature of step S1 is 10-40°C.

[0054] The reaction in step S1 is a reflux reaction.

[0055] According to some embodiments of the present invention, step S1 further comprises mixing the obtained mixture with water, removing the organic solvent and washing impurities after the reaction.

[0056] The mixing time with water is 30 to 120 minutes, for example, about 60 minutes or about 90 minutes. The amount of water added is 20 to 200% of the volume of the organic solvent used in step S1, for example, about 50%, 100% or about 150%. The sulfonation reaction process is terminated, and a sponge-like solid substance appears in the obtained mixture.

[0057] Methods for removing the organic solvent include distillation under reduced pressure.

[0058] The method for washing impurities comprises washing the sponge-like solid with pure water until the pH of the washing liquid is between 6.5 and 7.5, for example, about 7.0.

[0059] When the battery binder is used in an organic solvent system, for example, when the electrode active material is sensitive to water, step S2 also includes drying after the washing. The drying temperature is 60 to 100° C. For example, it can be about 70° C., 80° C. or about 90° C.

[0060] According to some embodiments of the present invention, in step S2, the base includes at least one of sodium hydroxide, lithium hydroxide and potassium hydroxide.

[0061] According to some embodiments of the present invention, in step S2, the alkali is used in the form of an aqueous alkali solution, and the mass concentration of the aqueous alkali solution is 1-10%, for example, about 3%, 5% or about 8%.

[0062] According to some embodiments of the present invention, in step S2, the amount of the base added is determined by the required content ratio of -SO3M in the grafted group.

[0063] According to some embodiments of the present invention, in step S2, the reaction time is 0.5 to 4 hours, for example, about 1 hour, 2 hours or about 3 hours.

[0064] According to some embodiments of the present invention, in step S2, the reaction comprises dissolving the sulfonated SEBS in a dispersant and mixing it with the base.

[0065] When the battery binder is used in an aqueous system, that is, to be prepared into an aqueous glue solution, the dispersant is a mixture of water and an organic solvent; the process of dissolving the sulfonated SEBS in the dispersant includes first dissolving the sulfonated SEBS in an organic solvent and then adding water for dispersion; the amount of the organic solvent used is based on the amount that can just dissolve the sulfonated SEBS; the organic solvent used includes at least one of an ether solvent, a ketone solvent and an ester solvent. Specifically, it includes at least one of tetrahydrofuran and N-methylpyrrolidone; the amount of water added is based on the concentration of the aqueous glue solution finally formed.

[0066] When the battery binder is used in an aqueous system, step S2 further includes removing the organic solvent that dissolves the sulfonated SEBS after the reaction, and the specific method includes vacuum distillation; the specific temperature of the vacuum distillation is 65-90°C.

[0067] When the battery binder is used in an oily system, that is, to be prepared into an oily adhesive, the dispersant includes at least one of an ether solvent, a ketone solvent and an ester solvent, and specifically includes at least one of tetrahydrofuran and N-methylpyrrolidone.

[0068] According to some embodiments of the present invention, the mass concentration of the aqueous glue and / or the oily glue is 5-15%, for example, about 8%, 10% or about 12%.

[0069] According to the above description, the preparation method provided by the present invention can directly prepare the aqueous adhesive or oily adhesive of the battery binder; if it is convenient for storage, it can also be evaporated to dryness and then dispersed again.

[0070] According to an embodiment of the third aspect of the present invention, an electrode is provided, wherein the raw materials for preparing the electrode include the battery binder.

[0071] Since the electrode adopts all the technical solutions of the battery binder of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.

[0072] According to some embodiments of the present invention, the electrode includes a positive electrode and / or a negative electrode.

[0073] According to some embodiments of the present invention, when the electrode comprises a current collector and an active coating covering a surface of the current collector;

[0074] The active coating includes active material, conductive agent and binder;

[0075] In the active coating, the active material includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, sodium nickel manganese titanate, graphite, hard carbon, silicon oxygen material and silicon carbon material. There is no strict restriction on the type of active material, as long as it is a positive electrode active material and a negative electrode active material that can be commercially used to prepare lithium ion batteries or sodium ion batteries. In actual production, if the active material is a commonly used negative electrode active material, the electrode is a negative electrode; otherwise, the electrode is a positive electrode.

[0076] In the active coating, the mass percentage of the active substance is 85-97%, for example, about 90%, 92%, 93%, 94%, 95% or about 96%.

[0077] In the active coating, the mass percentage of the binder is 1.5-5%, for example, about 2%, 3% or about 4%.

[0078] The adhesive includes the battery adhesive provided by the embodiment of the first aspect of the present invention.

[0079] The binder includes CMC and the battery binder provided by the first embodiment of the present invention. The mass ratio of CMC to the battery binder is 0 to 2:1. For example, it can be about 1:1 or about 0.5:1.

[0080] According to some embodiments of the present invention, the electrode is prepared by mixing and dispersing the active material, the conductive agent, the binder and the solvent to obtain a slurry, and then coating the slurry on the surface of the current collector and drying it.

[0081] The solvent used includes at least one of water and NMP. That is, the battery binder provided by the present invention is applicable to aqueous systems and oily systems. In actual production, a suitable solvent can be selected for homogenization according to the sensitivity of the active substance to water.

[0082] According to an embodiment of the fourth aspect of the present invention, a secondary battery is provided, wherein raw materials for preparing the secondary battery include the battery binder described in the embodiment of the first aspect of the present invention, or include the electrode described in the embodiment of the third aspect of the present invention.

[0083] Since the secondary battery adopts all the technical solutions of the battery binder or electrode of the above embodiments, it at least has all the beneficial effects brought by the technical solutions of the above embodiments.

[0084] According to some embodiments of the present invention, the secondary battery includes at least one of a sodium ion battery and a lithium ion battery.

[0085] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.

[0086] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values ​​2 and 3.

[0087] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0088] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0089] Figure 1 1 is the first week charge and discharge curve of the secondary battery in Example 5 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0090] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0091] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0092] Example 1

[0093] This example prepares a battery binder (referred to as S-SEBS) and provides a secondary battery including the battery binder. The specific process is as follows:

[0094] S1. dissolving SEBS in chloroform, and reacting the formed SEBS solution with a sulfonating agent to obtain sulfonated SEBS; wherein,

[0095] The preparation process of sulfonated SEBS is as follows:

[0096] The SEBS used in this example was purchased from Baling Petrochemical, and the specific model, monomer content and other information are shown in Table 1.

[0097] The concentration of the SEBS solution is 10 wt %; the solvent is chloroform.

[0098] The sulfonating agent is a mixture of acetic anhydride (CAS: 108-24-7) and concentrated sulfuric acid (CAS: 7664-93-9) with a concentration of ≥ 98 wt % in a 1:1 molar ratio;

[0099] The molar amount of acetic anhydride is 1.0 times the molar amount of SEBS.

[0100] The sulfonation reaction time was 6 h and the temperature was 25 °C.

[0101] After the sulfonation reaction was completed, water was added to the obtained mixed system and stirred for 60 minutes to terminate the sulfonation reaction; the amount of water added was equivalent to the volume of chloroform in the SEBS solution.

[0102] Then, the chloroform used to dissolve SEBS was removed by distillation under reduced pressure, and the solid product was washed with water until the pH value was within the range of 6.5 to 7.5;

[0103] After washing, dry at 100°C to constant weight (this step is performed for the convenience of testing; in actual production, if the process is mature, this step can be omitted).

[0104] S2. Dissolve sulfonated SEBS in tetrahydrofuran to form a solution, add pure water to adjust the concentration of the glue solution; and react the obtained solution with an alkaline aqueous solution for 2 hours.

[0105] The mass concentration of sulfonated SEBS in a mixed solution of water and tetrahydrofuran is 10%.

[0106] The aqueous alkali solution was a 5 wt % sodium hydroxide aqueous solution.

[0107] The amount of the aqueous alkaline solution to be added is determined by referring to the required alkalization rate in Table 1.

[0108] The reaction mixture was distilled under reduced pressure at 80°C to remove tetrahydrofuran, and a sulfonated SEBS aqueous gel solution (directly used for subsequent electrode material homogenization, referred to as S-SEBS) was obtained, and the concentration of the aqueous gel solution was 12wt%;

[0109] In the secondary battery provided in this example, the parameters of the positive electrode are shown in Table 2;

[0110] The electrolyte is: the solute is NaPF6, the concentration is 1 mol / L, and the solvent is EC, PC and DEC in a volume ratio of 1:1:1;

[0111] The battery model is: CR2025 button battery.

[0112] Example 2

[0113] This example prepares a battery binder and provides a secondary battery including the battery binder. The specific process is different from that of Example 1 in that:

[0114] In secondary batteries, the composition of the positive electrode slurry is different, and the specific differences are shown in Table 2.

[0115] Example 3

[0116] This example prepares a battery binder and provides a secondary battery including the battery binder. The specific process is different from that of Example 1 in that:

[0117] (1) In step S2, the alkaline aqueous solution used is an aqueous solution of lithium hydroxide with equal molar concentration and equal amount.

[0118] (2) Keeping the concentration of the final oily glue solution unchanged, the mixture of tetrahydrofuran and water in step S2 is replaced by a corresponding amount of NMP.

[0119] (3) In secondary batteries, the composition of the positive electrode slurry and some parameters of the negative electrode are different. The specific differences are shown in Table 2.

[0120] (4) Correspondingly, the electrolyte of the secondary battery is different, specifically: the solute is LiPF6, the concentration is 1 mol / L, and the solvent is EC, PC and DEC in a volume ratio of 1:1:1.

[0121] Example 4

[0122] This example prepares a battery binder and provides a secondary battery including the battery binder. The specific process is different from that of Example 1 in that:

[0123] (1) In secondary batteries, some parameters of the positive electrode and the negative electrode are different. The specific differences are shown in Table 2.

[0124] Example 5

[0125] This example prepares a battery binder and provides a secondary battery including the battery binder. The specific process is different from that of Example 3 in that:

[0126] (1) In secondary batteries, some parameters of the positive electrode and the negative electrode are different. The specific differences are shown in Table 2.

[0127] Example 6

[0128] This example prepares a battery binder and provides a secondary battery including the battery binder. The specific process is different from that of Example 1 in that:

[0129] (1) In secondary batteries, the positive electrode active materials and ingredient compositions are different. The specific differences are shown in Table 2.

[0130] (2) Keeping the concentration of the final glue solution unchanged, the mixture of tetrahydrofuran and water in step S2 is replaced by a corresponding amount of NMP.

[0131] Example 7

[0132] This example prepares a battery binder and provides a secondary battery including the battery binder. The specific process is different from that of Example 1 in that:

[0133] (1) In step S1, the molar amount of acetic anhydride is 1.3 times the molar amount of SEBS.

[0134] (2) In step S2, the amount of the alkaline aqueous solution added is different and is specifically determined by the alkalinity rate required in Table 1.

[0135] (3) The solid content of the positive electrode slurry is slightly different.

[0136] Example 8

[0137] This example prepares a battery binder and provides a secondary battery including the battery binder. The specific process is different from that of Example 1 in that:

[0138] (1) In step S1, the molar amount of acetic anhydride is 1.6 times the molar amount of SEBS.

[0139] (2) In step S2, no alkaline aqueous solution is added.

[0140] (3) The solid content of the positive electrode slurry is slightly different.

[0141] Example 9

[0142] This example prepares a battery binder and provides a secondary battery including the battery binder. The specific process is different from that of Example 1 in that:

[0143] (1) In step S1, the molar amount of acetic anhydride is 2.0 times the molar amount of SEBS.

[0144] (2) The solid content of the positive electrode slurry is slightly different.

[0145] Example 10

[0146] This example prepares a battery binder and provides a secondary battery including the battery binder. The specific process is different from that of Example 1 in that:

[0147] (1) In step S1, the SEBS used is synthesized in the laboratory, and its parameters such as molecular weight are different, see Table 1.

[0148] (2) In step S1, the molar amount of acetic anhydride is 1.7 times the molar amount of SEBS.

[0149] (3) In step S2, no alkaline aqueous solution is added.

[0150] (4) In secondary batteries, the positive electrode composition is different, and the specific differences are shown in Table 2.

[0151] Embodiment 11

[0152] This example prepares a battery binder and provides a secondary battery including the battery binder. The specific process is different from that of Example 1 in that:

[0153] (1) In step S2, the amount of the alkaline aqueous solution added is based on an alkalization rate of 100%.

[0154] Comparative Example 1

[0155] This example provides a secondary battery, which is different from Example 5 in that:

[0156] Excluding the preparation process of the battery binder, the composition of the negative electrode of the secondary battery is slightly different, and the specific differences are shown in Table 2.

[0157] Comparative Example 2

[0158] This example provides a secondary battery, which is different from Example 6 in that:

[0159] Excluding the preparation process of the battery binder, the composition of the secondary battery positive electrode is slightly different, and the specific differences are shown in Table 2.

[0160] Comparative Example 3

[0161] This example provides a secondary battery, which is different from Example 6 in that:

[0162] Excluding the preparation process of the battery binder, the composition of the secondary battery positive electrode is slightly different, and the specific differences are shown in Table 2.

[0163] Comparative Example 4

[0164] This example provides a secondary battery, which is different from the embodiment in that:

[0165] Excluding the preparation process of the battery binder, the composition of the secondary battery positive electrode is slightly different, and the specific differences are shown in Table 2.

[0166] Comparative Example 5

[0167] This example provides a secondary battery, which is different from the embodiment in that:

[0168] Excluding the preparation process of the battery binder, the composition of the secondary battery positive electrode is slightly different, and the specific differences are shown in Table 2.

[0169] Table 1 Parameters of the battery binder obtained in the example and the binder used in the comparative example

[0170]

[0171]

[0172] Table 2 Partial parameters of secondary batteries provided in Examples and Comparative Examples

[0173]

[0174]

[0175] In Table 2, 1-active material ratio-rubber ratio=conductive agent ratio; in the examples and comparative examples, the conductive agent used is SP conductive carbon black.

[0176] In Table 2, the glue ratio is based on the solid mass of the glue added.

[0177] Test Case

[0178] In the first aspect of this example, the performance of the battery binder obtained / used in the examples and comparative examples was tested, and the testing method was:

[0179] Sulfur content: The sulfonated SEBS obtained in step S1 is washed and dried, and then tested using a carbon-sulfur analyzer;

[0180] Sulfonation rate: convert the sulfur content obtained by the test into the molar content of benzenesulfonate and divide it by the molar content of styrene in the raw material to get the sulfonation rate;

[0181] Alkalization rate: The alkalinization rate is obtained by dividing the molar number of the added base by the molar number of the sulfonic group;

[0182] Molecular weight: tested by gel permeation chromatography;

[0183] The tensile strength at break is obtained by testing according to the standard document numbered GB / T 528-92.

[0184] The elongation at break is obtained by testing according to the standard document numbered GB / T 528-92.

[0185] Heat deformation temperature: After drying the battery binder, make it into small pieces of 10*30*2mm and hang them up with 30mm in the vertical direction. After 24 hours at different temperatures, measure the vertical dimensional change. The temperature when the dimensional change rate is greater than 0.5% is the heat deformation temperature.

[0186] The test results are shown in Table 1.

[0187] The results in Table 1 show that if other parameters are kept unchanged and the sulfonation rate is increased (Example 1 and Example 9), the tensile strength and elongation at break of the obtained battery binder decrease, while the heat deformation temperature increases. The reason is that after the sulfonation degree of the polymer increases, the hard segment micro-regions increase, resulting in an increase in the hardness of the polymer, the elongation of the molecular chain is limited, the tensile strength decreases, and the elongation also decreases, but the sulfonic acid group improves the heat resistance of the hard segment micro-region, and the heat deformation temperature of the polymer increases. The increase in the sulfonation rate increases the polarity of the polymer, which is conducive to bonding and also increases the electrical conductivity of the polymer. However, too high a sulfonation rate will cause the polymer to become brittle and reduce the processing performance of the pole piece.

[0188] If other parameters are kept equal, increasing the molecular weight of the raw material SEBS (Example 10) can mainly increase the viscosity of the battery slurry, so that a pole piece with good performance can be produced without using CMC as a thickener.

[0189] If other parameters are kept unchanged and the type of M in -SO3M is changed (Examples 1 to 6), the overall performance of the obtained battery binder is slightly different, but the change is very small. It can be seen that the present invention can make the obtained battery binder adapt to the environment of lithium secondary batteries, sodium secondary batteries or potassium secondary batteries by adjusting the type of M.

[0190] If other parameters are kept unchanged and the alkalization rate is increased (Example 1 and Example 11), the elasticity of the resulting battery binder becomes poor.

[0191] If the sulfonation rate and the alkalization rate are increased simultaneously (Example 1 and Example 7), the trend is equivalent to the trend of increasing the sulfonation rate alone.

[0192] If all parameters are equivalent, the performance results of the obtained battery adhesive, such as strength and thermal deformation, will be equivalent.

[0193] In the second aspect of this example, the electrochemical performance of the secondary batteries obtained in the examples and comparative examples and the phenomena in the preparation process were tested. The specific test conditions and test results are shown in Table 3. The percentage of 5C / 1C refers to the ratio of the discharge gram-to-capacity obtained by discharging at different rates under 0.2C charging. In the tests of Examples 1 to 2, 6 to 11, and Comparative Examples 2 to 5, the 1C current was set to 120mA / g, and the voltage range was 2.5 to 4.3V. In Example 3, the 1C current was set to 160mAh / g, and the voltage range was 2.0 to 3.75V. The above Examples and Comparative Examples were all charged and discharged at 0.1C for the first cycle, and the gram capacity was based on the first cycle, the cycle current was 1C charge and discharge, and the number of cycles was 100 weeks; in Example 4, Example 5 and Comparative Example 1, the 1C current was set to 330mAh / g, the voltage range was 0 to 2.5V, and 0.1C was used to discharge to 0V, and after standing for 5 minutes, 0.015C was used to discharge to 0V again, and after standing for 5 minutes, 0.1C was used to charge to 2.5V; this example also determined and compared the charge and discharge platforms of Example 5 and Comparative Example 1 through the charge and discharge curves of the first week. For all Examples and Comparative Examples, the slurry effects were visually observed.

[0194] Table 3 Electrochemical performance of the secondary batteries obtained in the examples and comparative examples

[0195]

[0196]

[0197] The results in Table 3 show:

[0198] The battery binder provided in the embodiment of the present invention can be applied to aqueous environments as well as oily environments; can be used as a binder alone or in combination with other common binders; can be used in the preparation of positive electrodes as well as negative electrodes; can be applied to lithium ion batteries as well as sodium ion batteries. It can be seen that the battery binder provided in the present invention has a wide range of applications.

[0199] Comparing the results of Examples 1 to 2, it can be seen that in the aqueous environment of the positive electrode of the sodium ion battery, if the content of S-SEBS in the binder is increased, even if the solid content is increased to a certain extent, the viscosity of the slurry is low, and the viscosity of the slurry may affect the process of the positive electrode of the sodium ion battery to a certain extent, and then affect the performance expression of the positive electrode in a small range; when the specific slurry viscosity is low, the fluidity will be too good during coating, and the natural flow of the slurry will cause uneven thickness of the pole piece. It should be noted that S-SEBS itself has sufficient adhesion, so in actual production, the viscosity of the obtained slurry can be adjusted by increasing the solid content of the slurry, or adding a small amount of binder with thickening effect such as CMC; however, simply increasing the solid content may cause the slurry to settle quickly and stratify.

[0200] By comparing Example 1 and Example 7, it can be seen that increasing the sulfonation rate and the alkalization rate at the same time can improve the first efficiency of the secondary battery, and the rate performance remains almost unchanged, but the cycle performance decreases slightly. This is because the alkali metal ions provided by the alkalization can improve the first efficiency, and regardless of whether it is alkalized, the sulfonic group has the ability to improve the ionic conductivity, so the first efficiency and rate performance are improved; however, when the sulfonation rate and the alkalization rate are increased at the same time, the brittleness of the battery binder becomes higher, the physical properties of the pole piece decrease, and it is more easily damaged after being subjected to stress shock during the cycle.

[0201] Comparing Example 1 and Example 8, it can be seen that when the sulfonation rate is increased and the alkalization rate is reduced, the performance of the secondary battery is slightly reduced. This is because after the battery binder is alkalized, the sodium ions or lithium ions it contains can be supplemented into the battery system, which is beneficial to improve the first efficiency. Therefore, if the alkalization is not performed, the first efficiency will decrease, and the increase of the sulfonate group reduces the physical properties of the electrode, resulting in a decrease in the cycle.

[0202] Comparing Example 1 and Example 9, it can be seen that increasing the sulfonation rate will improve the rate performance and cycle performance of the battery to a certain extent. This is because the increase in the sulfonation rate is equivalent to increasing the total amount of sulfonic groups, which will improve the ionic conductivity to a certain extent.

[0203] By comparing Example 8 and Example 10, it can be seen that after increasing the molecular weight of the SEBS raw material, in actual production, the slurry with a suitable viscosity can be obtained by increasing the solid content of the slurry, and there is no need to add a thickener such as CMC. Moreover, the overall performance of the battery is slightly improved by using the battery binder provided by the present invention alone.

[0204] By comparing the results of Example 1 and Example 11, it can be seen that the increase in the alkalization rate will lead to the deterioration of the electrode quality and affect the cycle. If the alkalization rate is too low, the first cycle will consume Na ions or Li ions, thereby reducing the initial effect.

[0205] The comparison of the results of Example 6 and Comparative Examples 2 to 5 shows that the battery binder provided by the present invention can significantly improve the capacity and initial efficiency of the battery; compared with unmodified SEBS and conventional maleic anhydride-modified SEBS, the battery binder provided by the present invention can further improve its cycle performance and rate performance due to increased ion conductivity and adhesion. Compared with traditional PVDF, when PVDF is used as a binder, there is about a 50% probability that the slurry may form jelly. The battery binder provided by the present invention can significantly avoid the problem of uniform jelly, significantly improve the yield of the battery and simplify the process. Compared with the binder used in Comparative Examples 2 to 4, the battery binder provided by the present invention can be used in an aqueous environment, has a wider range of application conditions, and has lower requirements on battery process conditions.

[0206] By comparing Example 5 with Comparative Example 1, it can be seen that the battery binder provided by the present invention can reduce the charging platform and increase the discharging platform. The battery binder provided by the present invention can greatly improve the polarization and reduce the internal resistance due to the increased ion conductivity. From the charge and discharge curve, it can be seen that the discharge capacity of the first curve 0.1C segment of Example 5 is higher than the total discharge capacity of Comparative Example 1. The discharge average voltage of Example 5 is 0.1259V and the charge average voltage is 0.1861V. The discharge average voltage of Comparative Example 1 is 0.0920V and the charge average voltage is 0.1970V. The specific charge and discharge results are as follows: Figure 1 shown.

[0207] In summary, the battery binder provided by the present invention has a wide range of applications, can improve ionic conductivity, does not contain corrosion / pollution factors such as F, and also has good heat resistance and aging resistance. Therefore, it is widely used in the positive and negative electrodes of secondary batteries such as lithium secondary batteries and sodium secondary batteries, and is suitable for various types of positive and negative electrode active materials, and the secondary batteries prepared have excellent electrochemical properties such as capacity, cycle and rate. It is precisely because of the above advantages that the secondary battery provided by the present invention is expected to be widely used in the fields of power batteries, energy storage batteries and 3C small household appliances.

[0208] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A battery adhesive, characterized in that: The battery binder is sulfonated modified SEBS.

2. The battery binder according to claim 1, characterized in that: The battery binder includes a main chain and a grafted group; The main chain is SEBS, and the SEBS has a phenyl group; The grafted group is grafted onto the phenyl group and includes -SO3H and / or -SO3M.

3. The battery binder according to claim 2, characterized in that: In the battery binder, the grafting rate of the grafting group is 15-35%; and / or, when the grafting group includes -SO3M, M includes at least one of Li, Na and K.

4. The battery binder according to any one of claims 1 to 3, characterized in that: The tensile strength at break of the battery binder is 15-25 MPa; preferably, the elongation at break of the battery binder is 410-470%; preferably, the thermal deformation temperature of the battery binder is 115-130°C.

5. A method for preparing a battery binder according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1. reacting SEBS with a sulfonating agent to obtain sulfonated SEBS; Or, after step S1, perform step S2: S2. reacting the sulfonated SEBS with a base.

6. The preparation method according to claim 5, characterized in that: In step S1, the sulfonation reagent is a combination of acetic anhydride and concentrated sulfuric acid; or, the sulfonation reagent includes sulfur trioxide.

7. The preparation method according to claim 5, characterized in that: In step S2, the alkali includes at least one of sodium hydroxide, lithium hydroxide and potassium hydroxide.

8. An electrode, characterized in that: The raw materials for preparing the electrode include the battery binder as claimed in any one of claims 1 to 4.

9. The electrode according to claim 8, characterized in that The electrodes include a positive electrode and / or a negative electrode.

10. A secondary battery, characterized in that: The raw material for preparing the secondary battery includes the battery binder according to any one of claims 1 to 4, or includes the electrode according to claim 8 or 9.

Citation Information

Patent Citations

  • Binder composition for secondary battery electrode, slurry for secondary battery electrode, and secondary battery electrode

    JP2009004222A

  • Binder having high ionic conductivity, and lithium ion battery containing same

    WO2021259084A1

Cited By

  • Recycling method of waste sodium-ion battery positive electrode material

    CN121484273A